Effect of Cement Replacement by Rice Husk Ash on Soft Soil Stabilization - Yoobanpot, Naphol; Jamsawang , Pitthaya (Agriculture and Natural Resources, 2014)
The characteristics of soft soil improvement using cement and rice husk ash were studied. Compressive strength testing of stabilized soil was investigated with various curing times of 3, 7, 14 and 28 d. The correlation between strength development and reaction products was investigated using X-ray diffraction analysis after the strength tests and changes in the stabilized soil structure were investigated using scanning electron microscopy. The results revealed that the soil strength increased when the soil was stabilized with cement and partial replacement of cement with rice husk ash. The results indicated that 30% rice husk ash was the appropriate content for partial cement replacement to produce a stabilized soil strength of 424, 722, 915 and 1,126 kPa at 3, 7, 14 and 28 d curing, respectively. It was also found that the increase in the strength of the stabilized soil was relative to the formation of major reaction products such as calcium silicate hydrate.